Desain Rute Pelayaran Sistem Hub and Spoke (Studi Kasus: Wilayah Papua, Indonesia) - Natalia, Christine (Metris: Jurnal Sains dan Teknologi, 2016)
Currenctly Indonesia’s government policy is focusing on designing its marine transportation and port development for logistics distribution in Indonesia to take advantage of the sea lanes. This maritime transportation concept that called sea highway is a strategy to improve connectivity and revitalize national logistic system thoroughly, in the form of organizing a scheduled big vessel regularly from western to eastern Indonesia and vice versa. One of the route is a sea highway towards Papua. This route starts from the port of Tanjung Perak that carry goods to be distributed to other ports, including the port of Manokwari (Papua). Distribution of goods in Papua region is largely use airlines and some use the sea transport. The distribution pattern by ship in Papua using "point to point" pattern . This pattern of distribution is sending goods from one point to another without regard to the overall network shipping, causing the logistics’ cost to be expensive due to the inequality in the distribution. The purpose of this study is to design the sea shippingnetworkfor distribution of goods in Papua with the distribution pattern of "hub and spoke". The design of this sea shipping network using 11 ports comprising 3 hub ports and 8 feeder ports in Papua. This study resulted routes that can deliver the goods from hub port to the spokes and vice versa with optimal total distance and cost. The design of routes using a Genetic Algorithm with the help of software Matlab in order to produce either an optimal hub and spoke and a minimum cost for its network.